Durability of steel fibre-reinforced recycled coarse aggregate concrete. (30th January 2020) - Gao, Danying; Zhang, Lijuan; Zhao, Jun; You, Peibo
Highlights: The durability of SFRCAC was investigated through carbonisation, fast freeze–thaw, and chloride penetration tests. The durability test methods of the Chinese Standard were introduced in detail and compared with the related specifications of ASTM. With the same steel fibre volume fraction and a similar compressive strength, the replacement ratio of the recycled aggregate had little effect on the durability of the SFRCAC. Mass loss of 5% was not a suitable failure criterion for the fast freeze–thaw test of the SFRCAC. Abstract: Although steel fibre-reinforced recycled coarse aggregate concrete (SFRCAC) is a promising structural material owing to its good mechanical properties and minimal environmental impact, there are uncertainties regarding its durability. Carbonation resistance, freeze–thaw resistance, and chloride ion penetration experiments were performed to evaluate the effects of the recycled coarse aggregate (RCA) and the steel fibres on the durability of SFRCAC. The test results indicated that the durability of SFRCAC was more sensitive to the water–cement ratio than to the RCA replacement ratio. A lower water–cement ratio corresponded to a better durability of the SFRCAC. The compactness of the concrete matrix was the key factor influencing the durability of the SFRCAC. The durability performance of the SFRCAC increased as the volume fraction ( V f ) increased from 0% to 1.5% and decreased slightly as V f increased from 1.5% to 2%. Mass loss of 5% was not a suitable failure criterion for the fast freeze–thaw test of the SFRCAC. It was proven that SFRCAC has good durability and can be successfully applied to structural members with proper mixture design.